Borrelia wingmen: dispersal and maintenance of Borrelia burgdorferi s.l. by birds - Norte, A. C. (2018)
Lyme borreliosis, caused by Borrelia burgdorferi s.l., is the most prevalent vector-borne disease of moderate climates of the northern hemisfere. In Portugal, several Borrelia genospecies are present in questing ticks, which have different associations with vertebrate reservoir hosts and Lyme borreliosis etiology. To better understand disease risk it is necessary to evaluate the relationships among Borrelia genospecies, their tick vectors and vertebrate reservoir hosts.